(untitled) (Global Journal of Human-Social Science, 2024)
This article investigates the factors that affect online customers satisfaction from the perspective of Bangladesh The study is a descriptive type of research Data have been collected from 201 respondents who make online purchasing using a structured survey questionnaire For analyzing data frequency tables factor analysis and multiple regressions have been used The findings from factor analysis reveal that information availability convenience ease of use attractive website design and customization of product or service affect online customers satisfaction mostly The study from multiple regression analysis reveals that there is a high degree of positive correlation between dependent variable and independent variables The findings from multiple regression analysis reveal that product quality delivery quality after sales service and fair price are highly significant factors that affect online customers satisfaction in Bangladesh The results of this research is suitable for the online product sellers or online service providers as they can take ideas about which factors they need to take into consideration with greater importance and caution for online customers satisfaction in a developing country perspective like Bangladesh